The effect of thermo-mechanical treatments and external magnetic fields on the transport critical current of Cr, Mo and In substituted TI-1212 dip-coated tapes / Rohani Omar - Omar, Rohani (2007)
In this work, Tl-1212/Ag dip-coated (DC) tapes were fabricated using TI1212 superconducting powders prepared from different nominal compositions and subjected to different combinations of thermal and mechanical treatments. The effects of the thermo-mechanical treatment on the transport critical current density (Jc) in zero field and low magnetic fields were investigated. The superconducting powder prepared with nominal compositions Tl0.9Cr0.1Sr2Ca0.9Pr0.1Cu2O7 (In-tapes), Tl0.9Bi0.1Sr1.9Mo0.1Ca0.9Y0.1Cu2O7 (Mo-tapes) and Tl0.9Bi0.1Sr1.9In0.1Ca0.9Y0.1Cu2O7 (In-tapes) which were synthesized by conventional solid state method. In the DC technique, silver strips were dipped into slurry made from mixture of superconducting powder, solvent, binder and dispersant. Some of the resulting tapes were subjected to mechanical rolling to investigate the effect of rolling on 1212 phase formation, critical temperature, TC and critical current density (Jc) of the tapes. For Cr-tapes, reannealing at > 870 °C caused higher Tl, evaporation resulted in lower 1212 volume % and produced partial melted microstructure. By considering the volume % of 1212, Tc and Jc, annealing at 870 °C was the best heat treatment to produce reasonable Jc. The higher magnitude of JC is attributed to the enhancement of grains contact within the core of the tapes as observed form its microstructure. For Mo-tapes, it was observed that different thermomechanical treatment on the tapes resulted in different values of Jc. JC enhancement was observed for tapes annealed at 2 870° C in combination with mechanical rolling. The results show that re—annealing at 2 870° C improves 1212 phase formation and Jc for Mo-tapes. However annealing at lower temperature caused the presence of higher amount SrCO3. The best performance in external magnetic field was observed for rolled tapes annealed at 910° C. For In-tapes, annealing at higher temperature improves 1212 phase and reduced SrCO3 content. The presence of SrC03 may be the other reason for lower Tc and Jc values. The performance of JC in magnetic field was limited by weak links. However, the development of strong links was much easier for In-tapes compared to Mo-tapes. In general, mechanical rolling promotes grains connectivity and improves intergranular connectivity. It was observed that appropriate annealing temperature in combination with rolling improves 1212 phase, TC and Jc. However the presences of impurities limit the superconducting properties of the dip-coated tapes. Jc observed in this work are generally comparable to the values of Tl-1212 tapes using powder-in—tube (PIT) method.